2016
DOI: 10.1111/ped.13136
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of imatinib in children with chronic myelogenous leukemia

Abstract: This study supports and confirms the need for monitoring the side-effects of IM treatment on growth, bone density and vitamin D status in pediatric CML. Prolonged IM treatment was associated with low BMD without disturbing bone parameters. There was high prevalence of vitamin D insufficiency. Therefore, the beneficial effect of vitamin D supplement should be explored with regard to the effects on height velocity and BMD in CML patients with vitamin D insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
2
28
0
1
Order By: Relevance
“…Children diagnosed with CML who are treated with TKI, specifically imatinib, demonstrate varying degrees of growth restriction. The decrease in Ht-SD appears to be more significant when treatment is initiated prior to the onset of puberty [56, 57] and may result in declines to heights less than 2 SD below the mean [56, 58]. At the onset of puberty, an increased growth velocity is often noted in children treated with TKI.…”
Section: Growth Impairment and Short Adult Height In Ccs Treated Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Children diagnosed with CML who are treated with TKI, specifically imatinib, demonstrate varying degrees of growth restriction. The decrease in Ht-SD appears to be more significant when treatment is initiated prior to the onset of puberty [56, 57] and may result in declines to heights less than 2 SD below the mean [56, 58]. At the onset of puberty, an increased growth velocity is often noted in children treated with TKI.…”
Section: Growth Impairment and Short Adult Height In Ccs Treated Withmentioning
confidence: 99%
“…At the onset of puberty, an increased growth velocity is often noted in children treated with TKI. However, there is limited and conflicting data on the net loss in growth potential at the final adult height in these survivors, as final adult heights are unavailable in most studies [56, 58, 59]. The precise mechanism for the growth impairment in children treated with TKI is unclear but it may be due to disrupted GH signaling [60], inadequate signal transduction through the IGF1-receptor (a tyrosine kinase receptor), or inhibition of PDGF-R signaling and disrupted chondrocyte recruitment at the growth plates [61].…”
Section: Growth Impairment and Short Adult Height In Ccs Treated Withmentioning
confidence: 99%
“…Prolonged imatinib treatment is associated with significantly diminished vitamin D 3 synthesis (13) leading to low bone mineral density, which may effectively mask other relevant bone parameters. For this reason, there is an urgent need for monitoring vitamin D3 levels in paediatric patients under continuous imatinib treatment (14). All our patients were carefully monitored for vitamin D3 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib is a tyrosine kinase inhibitor (TKI) approved for the treatment of chronic myelogenous leukaemia (CML), gastrointestinal stromal tumours and other uncommon haematologic malignancies. In a small study of children with CML, imatinib treatment appeared to reduce linear growth . Consistent with these results, a pre‐clinical young rodent model showed that continuous imatinib exposure was associated with dose‐dependent reductions in long‐bone length and BMD, as well as decreased resistance to fracture and lower circulating levels of the bone formation marker osteocalcin .…”
Section: Haematologic Malignanciesmentioning
confidence: 99%